2021
DOI: 10.7759/cureus.20334
|View full text |Cite
|
Sign up to set email alerts
|

A Man With Recurrent Pneumonitis: A Rare Case of Interstitial Lung Disease Associated With Anti-Mi-2 Beta-Specific Dermatomyositis

Abstract: Dermatomyositis (DM) and polymyositis (PM) are idiopathic inflammatory myopathies. Interstitial lung disease (ILD) develops in most patients with DM and PM directly related to morbidity and mortality. Diagnosis requires a myositis panel and high-resolution computed tomography (HRCT). Prognosis depends on specific myositis-specific antibodies and the pattern of the interstitial lung changes. Anti-Mi-2 antibody-specific dermatomyositis has a lower prevalence of interstitial lung disease and has a favorable progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…A longitudinal study of anti-Mi-2 patients in the United States found only 3 patients out of 58 developed features of ILD ( 70 ). Literature search revealed a case report from the United States of a patient with persistent dry cough and dyspnea who was found to have bibasilar infiltrates on CXR and bilateral patchy ground glass infiltrates on HRCT, with serial imaging revealing of organizing pneumonia, in addition to the development of progressive proximal myopathy in the presence of anti-Mi-2 antibody positivity ( 74 ).…”
Section: Dermatomyositismentioning
confidence: 99%
“…A longitudinal study of anti-Mi-2 patients in the United States found only 3 patients out of 58 developed features of ILD ( 70 ). Literature search revealed a case report from the United States of a patient with persistent dry cough and dyspnea who was found to have bibasilar infiltrates on CXR and bilateral patchy ground glass infiltrates on HRCT, with serial imaging revealing of organizing pneumonia, in addition to the development of progressive proximal myopathy in the presence of anti-Mi-2 antibody positivity ( 74 ).…”
Section: Dermatomyositismentioning
confidence: 99%